Identification of Inhibiting Factors as a basis for Formulating Strategies to Tackle HIV/AIDS in Tulungagung Regency, Indonesia - Desy Puspitasari1 , Farida Handayani1 , Mamik Hidayah1 , Ratna Dwi Wulandari2 , Agung Dwi Laksono3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Based on the overall assessment, Indonesia has anticipated the epidemy of HIV/AIDS. However, thenumber of HIV/AIDS cases in Tulungagung District has increased a bit massively year by year. The totalcases of HIV/AIDS from 2006 to 2018 were 2320 cases. In the last three years, the number had an increaseof 295 cases, 324 cases, and 431 cases in 2016, 2017, and 2018 respectively. The high number of HIV/AIDScases showed that some obstacles still exist to combat the HIV/AIDS in Tulungagung District. To identifythe constraints as the basis of formulating strategies for the HIV/AIDS in Tulungagung District. We useda qualitative and descriptive method with an in-depth interview. Based on the in-depth interview, theinhibiting factors for HIV/AIDS prevention are divided into 3 factors. First, HIV/AIDS patients are stillclosed and reluctant to do medical check-ups and treatment in health facilities. Second, in terms of healthcare, health personnel still think that HIV/AIDS is an infectious disease that they keep away. Third, fromsociety’s perspective, the social stigma about HIV/AIDS sufferers often exists. By knowing the obstaclesthat occur in Tulungagung District, the right strategy can be made to accelerate HIV/AIDS prevention inTulungagung District.